2021
DOI: 10.3390/min11060603
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Metal Contaminants between Bulk and Fine-Grained Fraction in Freshwater Sediments: A Critical Appraisal

Abstract: The distribution of six common metal contaminants (Cd, Cr, Cu, Ni, Pb, Zn) in the bulk (<2 mm) and fine fractions (<63 µm) of freshwater sediments was compared to conclude on the long-existing dilemma which fraction should be used in the investigation of the metal contamination. The environments included in the study (24 rivers, 8 lakes) were very different with respect to sediments origin and composition and they provided a good review of the possible scenarios. For the river sediments, particularly tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The high proportion of fine-grained particles has been observed previously in the riverine and estuarine sediments of the region [4], and has been attributed to the intense weathering of Eocene flysch formations in the drainage area. When particles enter a stratified, saline, microtidal estuarine environment, rapid sedimentation occurs [19], reflected by the predominance of fine-grained sediments in the upper part and coarser sediments in the lower part of the estuary.…”
Section: Granulometric Characteristics Of Sedimentssupporting
confidence: 65%
See 1 more Smart Citation
“…The high proportion of fine-grained particles has been observed previously in the riverine and estuarine sediments of the region [4], and has been attributed to the intense weathering of Eocene flysch formations in the drainage area. When particles enter a stratified, saline, microtidal estuarine environment, rapid sedimentation occurs [19], reflected by the predominance of fine-grained sediments in the upper part and coarser sediments in the lower part of the estuary.…”
Section: Granulometric Characteristics Of Sedimentssupporting
confidence: 65%
“…The Raša River estuary is a region of intense deposition of fine-grained, mostly clayey particles derived from Eocene clastic flysch sediments, and represents a river-dominated disequilibrium estuary [4]. Most of the particles (90%) carried into the estuary by the Raša River are suspended solids, and at the head of the estuary this fine-grained material is flocculated and preferentially accumulates, creating a progradation delta [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although the values of PLI at location S1 (0.832–0.911) were somewhat lower than values at location S2 (1.006–1.073) ( Table S10 ), all of the PLI values were lower than or close to 1, indicating unpolluted sediment. Values at location S2 were higher, probably because of the sedimentation of fine–coarse particles containing higher concentrations of metal(loid)s closer to the estuary [ 14 , 37 ]. Based on the concentrations of elements in sediments, their vertical profiles and calculated sediment indices (EF, Igeo , PLI), it can be concluded that the chemical composition of the analyzed stream sediments of the Raša River at both sites mostly reflects the geological and hydrogeological background of the catchment and that sediments are not significantly polluted with inorganic elements.…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations of trace elements in sediments quantified in that study (As, Cd, Cr, Co, Cu, Pb, Ni, and Zn) were higher at the discharge and downstream sites than at the upstream sites [24]. In addition, in the same study area, concentrations of potentially toxic elements (Cd, Cr, Cu, Ni, Pb, and Zn) were determined in the fine-grained fraction (<63 µm) and bulk of the sediment, and for all of these elements, except Ni [25], the values were below the Predicted No Effects Concentration (PNEC) [26].…”
Section: Introductionmentioning
confidence: 93%